Cybersecurity Regulation and Governance During the Pandemic Time in Indonesia and Singapore - Awaludin Marwan; Hee Jhee Jiow; Kevin Monteiro (International Journal of Global Community, 2022)
Discussing the cyber security regulation in Singapore and Indonesia, which delineating the role of cyber security agency and the cyber security policy in the era of pandemic is a pivotal component. Cyber security can investigate cyber incident which involved many victims and sensitive data. For instance, in June 2018, hackers breached the 1.5 million patient’s data of the SingHealth IT systems. In Indonesia, it was happened the data breach involved the voter personal data of general election. Despite, the agency had failed to arrest the cyber criminals, the prevention and reparation of IT security system in the critical infrastructure and public electronical good is very important. During the pandemic, people use the internet more and need to be secured.